Influence of the lubricated joint model on the dynamic response of multibody systems - Flores, Paulo (2006)
The influence of the lubricated joint model on the dynamic response of mechanical systems is investigated throughout this work. In the process, under the framework of the multibody systems formulation, a comprehensive methodology for modelling lubricated revolute joints is presented. This methodology uses the superposition principle for the load capacity due to the wedge effect entrainment and squeeze film effect separately. The hydrodynamic forces are obtained by integrating the pressure distribution evaluated with the aid of Reynolds’ equation written for the dynamic regime. The hydrodynamic forces are nonlinear functions of the journal centre position and of its velocity with reference to the bearing centre. The hydrodynamic forces built up by the lubricant fluid are evaluated from the state of variable of the system and included into the equations of motion of the mechanical system. Moreover, the main kinematic and dynamic aspects of the modelling of revolute joints with clearance are presented and discussed in this work in order to compare them with the lubricated joints. The numerical models for normal and tangential contact forces are reviewed. In a similar way to the lubricated model, in this case, the contact-impact forces developed during the contact are evaluated and introduced into the equations of motion of the mechanical system. The main assumptions and procedures adopted in this work are demonstrated through the numerical results obtained from computational simulations of a planar slider-crank mechanism, which includes a revolute joint with clearance. Furthermore, the global results produced with the different lubricated models are compared to those obtained when the revolute joint is modelled as a dry joint.